Determinan Tindakan Penagihan Aktif Terhadap Pencairan Tunggakan Pajak Pada KPP Pratama Karanganyar - Elisa Nur Aziza; Kartika Hendra Titisari; Dimas Ilham Nur Rois (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
Active tax collection action is a law enforcement action carried out by the Directorate General of Taxes so that Taxpayers pay off their tax arrears. This tax collection action also helps to secure tax revenues and prevent tax assessments from expiring. This research aims to test and analyze the effect of active tax collection actions in the form of letters of warning, forced letters, blocking of bank accounts, and confiscation of assets on the disbursement of tax arrears at KPP Pratama Karanganyar. The data used in this research is secondary data obtained from KPP Pratama Karanganyar. The sample used in this research was 100 taxpayers with the largest amount of tax arrears from 2018 to 2022. The data analysis technique used was descriptive statistical analysis and multiple linear analysis to test the research hypothesis. The results of this research show that letters of warning, letters of force, and confiscation of assets have an influence on the disbursement of tax arrears. Meanwhile, blocking bank accounts has no effect on disbursement of tax arrears. Keywords : Active Tax Collection Action; Disbursement Of Tax Arrears